Use of hazelnut kernel oil methyl ester and its blends as alternative fuels in diesel engines - (:unkn) unknown (My University, 2008)
Interest in vegetable oil as an alternative to diesel fuel in diesel engines has increased during the last few decades because reserves of petroleum fuel and its derivatives are diminishing rapidly, and because they have harmful effects on the environment. In this study, hazelnut (Corylus avellana L.) kernel oil was evaluated as an alternative fuel in diesel engines. Firstly, the optimum transesterification reaction conditions for hazelnut kernel oil, with respect to reaction temperature, volumetric ratio of reactants, and catalyst, were investigated. Secondly, an experimental investigation was carried out to examine performance and emissions of a direct injection diesel engine running on hazelnut kernel oil methyl ester and its blends with diesel fuel. Results showed that hazelnut kernel oil methyl ester and its blends with diesel fuel are generally comparable to diesel fuel, according to engine performance and emissions. © Tübi̇tak.
Keywords: Blends; Emissions; Hazelnut kernel oil methyl ester; Performance; Transesterification